Developmental differences in sensitivity to semantic relations among good and poor comprehenders: evidence from semantic priming. - Nation, K; Snowling, M (1999)
Semantic priming for category coordinates (e.g. CAT-DOG; AEROPLANE-TRAIN) and for pairs of words related through function (e.g. BROOM-FLOOR; SHAMPOO-HAIR) was assessed in children with good and poor reading comprehension, matched for decoding skill. Lexical association strength was also manipulated by comparing pairs of words that were highly associated with pairs that shared low association strength. Both groups of children showed priming for function-related words, but for the category co-ordinates, poor comprehenders only showed priming if the category pairs also shared high association strength. Good comprehenders showed priming for category-related targets, irrespective of the degree of prime-target association. These findings are related to models of language development in which category knowledge is gradually abstracted and refined from children's event-based knowledge and it is concluded that in the absence of explicit co-occurrence, poor comprehenders are less sensitive to abstract semantic relations than normal readers.